HEAT TOLERANT VARIETY KUFRI SURYA HAS HIGHER ANTI-OXIDANT CONTENT IN TUBERS EXPOSED TO HIGH TEMPERATURE - Kumar, Devendra; Chalkoo, S.; Singh, B P; Minhas, J S (Potato Journal, 2013)
Antioxidants like ascorbic acid, phenolic compounds, proline etc. play an important role in protecting plants exposed to abiotic stresses from oxidative damage to cell membranes and cell integrity. A comparison of antioxidant content in heat tolerant variety Kufri Surya and heat susceptible variety Kufri Ashoka was made in tubers exposed to 40oC. Kufri Surya had higher ascorbate content and there was no tuber rottage after 7 days of exposure to heat stress whereas tubers of Kufri Ashoka, which had lower ascorbate content showed high incidence of rottage. It is suggested that non-enzymatic molecules play an important role in mitigating the adverse effect of heat stress during germination of Kufri Surya tubers while such antioxidant defense mechanisms poorly operated in Kufri Ashoka leading to tissue disintegration.